The role of trust in mediating the effect of blockchain and e-payment on logistics 4.0 and supply chain capabilities in Thailand - Parinya Ruangtip; Wichien Rueboon; Khanitin Jornkokgoud; Md Faysal (Global Business & Finance Review (GBFR), 2024)
Purpose: This study investigates the intricate interplay among e-payment, blockchain, and trust dynamics and their impact on logistics 4.0 and supply chain capabilities within the context of Thailand. Design/methodology/approach: A sample population of 205 managers and executives from the logistics industry provided data, allowing for a robust analysis grounded in empirical evidence. Utilizing a causal model approach, the study employed structural equation modeling to evaluate the accuracy and fit of the theoretical framework to empirical data. Findings: Results revealed significant relationships, highlighting the pivotal role of trust as a mediator between e-payment, blockchain, and logistics capabilities. Specifically, while e-payment positively influences supply chain capabilities and trust, its direct impact on logistic 4.0 capabilities is insignificant. Conversely, blockchain technology directly fosters trust and indirectly enhances logistics 4.0 and supply chain capabilities. Furthermore, trust emerges as a critical factor influencing the effectiveness of logistics operations and plays a central role in fostering trans-parency and operational efficiency. Research limitations/implications: This underscores the importance of integrating blockchain technology to encour-age trust and collaboration across the supply chain. However, challenges such as the need for supportive policies and accounting guidelines for SMEs must be addressed to fully leverage the benefits of blockchain in Thailand's logistics industry. Originality/value: The findings emphasize the importance of secure payment infrastructures and blockchain technol-ogy in building trust and enhancing supply chain capabilities.
Keywords: 650; Industry 4.0; Digital systems; Tracking; Smart logistics; Transparent